Diseño del accionamiento electromecánico para un sistema de banda transportadora de mineral de hierro (2021)
It’s carried out the design process of an electromechanics drive system for a belt conveyor system for iron ore transportation at 2500 ton per hour. From the requirements in the driving pulley, it is chosen the most convenient drive system and it’s performed the detailed design of the mechanical components, such as the selection of the 250 kW electric motor and the electronic frequency inverter, the coupling from the motor to the gearbox and the coupling from the gearbox to the driving pulley, the selection of the backstop mounted in the pulley and the selection of the three gear stages parallel axis gearbox. It´s carried out the gear calculus following the ISO 6336:2006 standard and the fatigue strength-based analysis of the shafts. The design process ends with the assembly drawings of the whole drive system and the production drawings of the gearbox. It´s found that it exists a wide variety of alternatives of arrangement and equipment options, choosing one of the more optimal in terms of configuration, simplicity and safety.